The experiences of EMS providers taking part in a large randomised trial of airway management during out of hospital cardiac arrest, and the impact on their views and practice. Results of a survey and telephone interviews. (April 2020) - Kirby, K.; Brandling, J.; Robinson, M.; Thomas, M.; Voss, S.; Benger, J.
Abstract: Aims: To explore EMS experiences of participating in a large trial of airway management during out-of-hospital cardiac arrest (AIRWAYS-2), specifically to explore: 1. Any changes in views and practice as a result of trial participation. 2. Experiences of trial training. 3. Experiences of enrolling critically unwell patients without consent. 4. Barriers and facilitators for out-of-hospital trial participation. Methods: An online questionnaire was distributed to 1523 EMS providers who participated in the trial. In-depth telephone interviews explored the responses to the online questionnaire. Quantitative data were collated and presented using simple descriptive statistics. Qualitative data collected during the online survey were analysed using content analysis. Interpretive Phenomenological Analysis was used for qualitative interview data. Results: Responses to the online questionnaire were received from 33% of the EMS providers who participated in AIRWAYS-2, and 19 providers were interviewed. EMS providers described barriers and facilitators to trial participation and changes in their views and practice. The results are presented in five distinct themes: research process; changes in airway management views and practice; engagement with research; professional identity; professional competence. Conclusions: Participation in the AIRWAYS-2 trial was enjoyable and EMS providers valued the study training and support. There was enhanced confidence in airway management as a result of taking part in the trial. EMS providers indicated existing variability in training, experience and confidence in tracheal intubation, and expressed a preference for the method of airway management to which they had been randomised. There was support for the stepwise approach to airway management, but also concern regarding the potential loss of tracheal intubation from 'standard' EMS practice. The views and practices of the EMS providers expressed in this research will usefully inform the design of future similar trials.